2021
DOI: 10.1186/s12992-020-00653-5
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers’ involvement in the prevention and control of non-communicable diseases in Wakiso District, Uganda

Abstract: Background Community health workers (CHWs) are an important cadre of the global health workforce as they are involved in providing health services at the community level. However, evidence on the role of CHWs in delivering interventions for non-communicable diseases (NCDs) in Uganda is limited. This study, therefore, assessed the involvement of CHWs in the prevention and control of NCDs in Wakiso District, Uganda with a focus on their knowledge, attitudes and practices, as well as community per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…Working with community organisations that are embedded locally and hence offer more insight into their population’s needs, could foster more effective ways to optimise physical activity promotional campaigns [ 58 ]. Previous research has also highlighted the potential of community health workers undertaking public health promotion in Africa [ 59 ]. Physiotherapists could also collaborate with health workers to endorse physical activity within their locality.…”
Section: Discussionmentioning
confidence: 99%
“…Working with community organisations that are embedded locally and hence offer more insight into their population’s needs, could foster more effective ways to optimise physical activity promotional campaigns [ 58 ]. Previous research has also highlighted the potential of community health workers undertaking public health promotion in Africa [ 59 ]. Physiotherapists could also collaborate with health workers to endorse physical activity within their locality.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from many LMICs, including Ethiopia, suggests that task-sharing from physician to non-physician health workers (mostly nurse and community health workers) can address critical workforce shortages and increase access to essential NCD health services [41,42]. In other settings, such workers have been crucial in delivering health education and conducting early detection, case management, and lifestyle interventions to manage NCDs in the community [43][44][45]. Despite this evidence from elsewhere and the expectation of Ethiopia's HEWs to deliver NCD services, we found that their role was limited [7].…”
Section: Discussionmentioning
confidence: 99%
“…Given the issues around the affordability of private doctors and the lack of doctors in the public health sector, community health workers could be trained in screening those at risk and referring individuals for further management. Studies have shown that community health workers are effective in a number of public health programmes in various settings (44,45). In addition, mass screening camps for the early detection of HT cases can be considered in high risk areas with limited health facilities.…”
Section: Discussionmentioning
confidence: 99%